Roman rule in Greek and Latin writing : double vision - Madsen, Jesper Majbom.; Rees, Roger. (Impact of Empire, 2014)
Roman Rule in Greek and Latin Writing explores the ways in which Greek and Latin writers from the late 1st to the Third century CE experienced and portrayed Roman cultural institutions and power. The central theme is the relationship between cultures as reflected in Greek and Latin authors' responses to Roman power; in practice the collection revisits the orthodoxy of two separate intellectual groups, differentiated as much by cultural and political agenda as by language. The book features specialists in Greek and Roman literary and intellectual culture; it gathers papers on a variety of authors, across several literary genres, and through this spectrum, makes possible an informed and detailed comparison of Greek and Latin literary views of Roman power (in various manifestations, including military, religion, law and politics).